2007
DOI: 10.1080/03601230701465783
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of carbofuran and carbaryl on Oolong tea during tea bushes, manufacturing and roasting processes

Abstract: Carbofuran (2,3-dihydro-2,2-dimethyl-7-benzofuranol-N-methylcarbamate) and carbaryl (1-naphthyl-N-methylcarbamate) are insecticides widely used in tea plantations. The objective of the present study was to evaluate the dissipation of carbofuran and carbaryl during the growth periods of Oolong tea, processing and roasting. Analysis of the residual insecticides was carried out using high-pressure liquid chromatography with a post-column fluorescence detector. Results showed that in the tea field carbofuran dissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
2
4
1
Order By: Relevance
“…This attribution could be associated with the long hours (at least 1 h) of hot blasting at 80 °C. The result of the current work is in line with the observations of Wu et al and Grover et al, who found that drying leads to the dissipation of 29% carbaryl and 59% acenaphthene during oolong and black tea manufacturing. The loss of PAEs during spreading may be attributed to the long processing time (10–12 h) and fugacity of PAEs with a high vapor pressure and small molecular weight.…”
Section: Resultssupporting
confidence: 92%
“…This attribution could be associated with the long hours (at least 1 h) of hot blasting at 80 °C. The result of the current work is in line with the observations of Wu et al and Grover et al, who found that drying leads to the dissipation of 29% carbaryl and 59% acenaphthene during oolong and black tea manufacturing. The loss of PAEs during spreading may be attributed to the long processing time (10–12 h) and fugacity of PAEs with a high vapor pressure and small molecular weight.…”
Section: Resultssupporting
confidence: 92%
“…It shows that the degradation of sulfoxaflor residue is quickest under 37°C fermentation temperature. The trend was contrary with the reported paper (Wu, Chu, Wang, & Lur, 2007). It implied that enzyme catalysis may play an more important role in degradation of sulfoxaflor than thermal decomposition.…”
Section: Resultscontrasting
confidence: 96%
“…That may be due to the dissipation of carbamate pesticides during the growth, processing and roasting. [22] The surveyed result is similar to that of our previous reports for tea fresh-leaf samples. [23] The data also suggest that the residues of carbamate pesticides on field-sprayed tea plants can be dissipated almost completely when good agriculture practice (GAP) is followed by tea farmers.…”
Section: Evaluation the Carbamate Pesticides In Tea Samplesupporting
confidence: 90%